Measurement of the rate of b(b)over-bar-b(b)over-bar events in hadronic Z decays and the extraction of the gluon splitting into b(b)over-bar - Abreu, P; Adam, W; Adye, T; Adzic, P; Ajinenko, I; Albrecht, Z; Alderweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; Almehed, S; et al. (1999)
The rate Z → bb̄bb̄ was measured using about 2×106 hadronic decays collected by the DELPHI experiment in 1994 and 1995. Events were forced into 3-jets with ymin > 0.06 and a b-tag was required for every jet. The rate was measured to be: R4b = BR(Z → bb̄bb̄)/BR(Z → hadrons), = (6.0 ± 1.9(stst.)) ± 1.4(Syst.)) × 10-4 where the invariant mass of every bb̄ system is above twice the b quark mass. Using the value of R4b the probability of secondary production of a bb̄ pair from a gluon per hadronic Z decay, gbb, was extracted and found to be: gbb = (3.3 ± 1.0(stat) ± 0.8(syst.)) × 10-3. © 1999 Published by Elsevier Science B.V. All rights reserved.